Influence of crop sequencing and tree abundance on soil carbon pool in temperate agro-ecosystems of the Indian Himalayan region - Nautiyal, Prachi; Arunachalam, Kusum (Indian Journal of Agroforestry, 2023)
Soil carbon sequestration is a complex process that is influenced by several factors such as input of organic carbon into the soil, carbon losses from the soil, temperature, agricultural management practices (tillage), soil moisture, soil texture etc. In the present study, soil organic carbon and microbial biomass carbon were compared along a cropping sequence in the high altitudes of Indian Himalayan region. The soil organic carbon (SOC) and nitrogen percentages varied from 1.72 to 3.42 % and 0.23 to 0.388 % respectively, irrespective of the cropping systems. Legumes-based system maintained highest carbon content in the soil. Microbial biomass carbon (MBC) was highest in the fields planted with Glycine max (soybean) in kharif season and in Lens culinaris (252 μg/g) (legume) in the rabi season. A linear relationship was observed between MBC and SOC as well as between MBC and Dehydrogenase activity in both the cropping seasons. Observed trends in the labile fraction of soil organic carbon, i.e., the MBC also varied significantly among the cropping systems indicating the significance of crop sequence, crop mixtures and tree abundance in manifesting carbon sequestration process. The study highlights the importance of various agromanagement practices in the traditional croplands of Indian Himalayan region and thereby, assists in increasing crop productivity and simultaneously maintains soil fertility.